Food Security of Small-Scale Fishermen's Households in Prigi Bay, Trenggalek Regency - Pudji Purwanti; Mochammad Fattah; Agus Dwi Sulistyono (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
The dependence of fishermen on obtaining income during the fishing season can cause problems in fulfilling food needs. Therefore, this study aims to analyze the food security of small-scale fishermen's households. The sampling technique was a purposive sampling of 75 small-scale fishing households. The data analysis used was Jonsson and Toole's analysis of food expenditure, energy adequacy and food security. The results showed when it is not fish season or moderate season, some fishing households do productive activities outside of fishing, such as cultivating forest land belonging to the Indonesian Forestry Minister, becoming marine tour guides, and having livestock and a working wife. As a result, household income can meet basic food and non-food expenditures. The average level of energy consumption is 2,772.8 kcal/capita/day, and the average protein consumption is 177.8 grams/capita/day. The calories from grains or rice reach 780 kcal/capita/day, and the highest protein source comes from fish getting 140.7 grams/capita/day. All fisherman household respondents have a proportion of expenditure for food consumption less than sixty per cent and a gonad maturity level of more than eighty per cent. This value indicates that all small-scale fishing households are food insecure. The existence of activities outside of catching fish diversifies business in the household, enabling fishing households to meet the basic needs of food and non-food and food security.